2012
DOI: 10.1097/bpo.0b013e31823ab359
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Patterns of Scoliosis in Children With Multiple Pterygium Syndrome

Abstract: Level IV, Diagnostic Study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…A previous study reported that the prevalence of scoliosis in patients with MPS was 81.3% (13 of the 16 patients) [28]. A previous study reported that the prevalence of scoliosis in patients with MPS was 81.3% (13 of the 16 patients) [28].…”
Section: Discussionmentioning
confidence: 98%
“…A previous study reported that the prevalence of scoliosis in patients with MPS was 81.3% (13 of the 16 patients) [28]. A previous study reported that the prevalence of scoliosis in patients with MPS was 81.3% (13 of the 16 patients) [28].…”
Section: Discussionmentioning
confidence: 98%
“…[4,5] Although the results of surgical approaches for anomalies of neck zone and vertebral were described well, sufficient data is unavailable in the literature about surgical orthopedics approaches for anomalies in lower extremity with rehabilitation programs that were applied after the surgery. [4] The largest series were reported by Joo et al, [6] that described the prevalence of vertebral anomalies and surgical approach but not enough data was presented about lower extremity surgical approaches or their results. Bellamy et al [7] evaluated rehabilitation results of knee flexion contractures in seven cases without mentioning the surgical results.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of all forms of pterygium syndrome is uncertain and they are mostly non-specifically termed as arthrogryposis. The vast majority of previous publications on this entity are individual case reports [2,3,4,5]. …”
Section: Discussionmentioning
confidence: 99%
“…There are two forms of MPS: the Escobar type is a rare autosomal recessive disorder and is the milder of the two types. Lethal MPS is associated with stillbirth [2]. In this case report, we describe a 15-year-old female infant with Escobar syndrome (ES) presenting with abdominal pain of unknown aetiology.…”
Section: Introductionmentioning
confidence: 99%